Lost productivity and burden of illness in cancer survivors with and without other chronic conditions. Issue 18 (21st June 2013) - Dowling, Emily C.; Chawla, Neetu; Forsythe, Laura P.; de Moor, Janet; McNeel, Timothy; Rozjabek, Heather M.; Ekwueme, Donatus U.; Yabroff, K. Robin
<x xml:space="preserve">Abstract</x> BACKGROUND Cancer survivors may experience long‐term and late effects from treatment that adversely affect health and limit functioning. Few studies examine lost productivity and disease burden in cancer survivors compared with individuals who have other chronic conditions or by cancer type. METHODS We identified 4960 cancer survivors and 64, 431 other individuals from the 2008‐2010 Medical Expenditure Panel Survey and compared multiple measures of disease burden, including health status and lost productivity, between conditions and by cancer site for cancer survivors. All analyses controlled for the effects of age, sex, race/ethnicity, and number of comorbid conditions. RESULTS Overall, in adjusted analyses in multiple models, cancer survivors with another chronic disease (heart disease or diabetes) experienced higher levels of burden compared with individuals with a history of cancer only, chronic disease only, and neither cancer, heart disease, nor diabetes across multiple measures (P < .05). Among cancer survivors, individuals with short survival cancers and multiple cancers consistently had the highest levels of burden across multiple measures (P < .0001). CONCLUSIONS Cancer survivors who have another chronic disease experience more limitations and higher levels of burden across multiple measures. Limitations are particularly severe in cancer survivors with short survival cancer and multiple cancers. Cancer 2013;119:3393–401. © 2013 American Cancer Society.